Pengembangan Sistem ERP Modul Inventory untuk Proses Penyimpanan Alat Medis pada Instalasi Kedokteran Nuklir RSHS dengan Metode Quickstart - Divani Prajna Lutfiah; Ari Yanuar Ridwan; Umar Yunan Kurnia Septo Hediyanto; Kharisma Perdani Kusumahastuti (Jurnal Indonesia : Manajemen Informatika dan Komunikasi, 2024)
To improve the quality of hospital services, hospital operations can support this by following applicable standards so that the service process can run well and effectively. With the regulations related to the medical device storage system in hospitals, especially in service processes that pose a risk, such as the Nuclear Medicine Installation, a management system is needed that can regulate the flow of goods to and from the storage warehouse. One of the components used in the Nuclear Medicine Installation service process is a radioactive compound that has a risk in its use if unattended. This activity can cause problems to the surrounding environment, including patients or medical personnel, if there is no management that oversees the management of the entry and exit of goods from the warehouse. Therefore, a management process is needed to manage the storage of medical devices, including radioactive compounds used. All data can be centralized in one database so that related departments can use it to check the stock or availability of goods in the warehouse. This research will design an ERP-based medical device storage system with OpenSource Odoo using the QuickStart method. This solution is expected to help integrate parts in the Nuclear Medicine Installation and control risky compounds.